Saint Petersburg: On the Issue of the Strategy for the Development of Municipalities in Conditions of Economic and Political Uncertainty - A. D. Khlutkov; N. M. Mezhevich (Управленческое консультирование)
Saint Petersburg is the second largest and most important city in Russia, which is in a seaside and border situation. Its peculiarity is that, unlike Sevastopol — also a city of federal subordination, it is a complex collection of municipalities of different status. The multilevel strategies of the federal, regional and local level are a logical phenomenon from the point of view of theory, but very problematic for practical implementation. Abandoning strategic planning in the face of uncertainty is a gross managerial error. Adjustment of the municipal structure of St. Petersburg is not a fundamental problem, since it belongs to the competence of the authorities of the subject of the federation.